2014
DOI: 10.1016/s0254-6272(14)60100-x
|View full text |Cite
|
Sign up to set email alerts
|

Huogu I formula prevents steroid-induced osteonecrosis in rats by down-regulating PPARγ expression and activating Wnt/LRP5/β-catenin signaling

Abstract: The results of our present study highlight the lipid-lowering potential of Huogu I formula, and provide further evidence of the involvement of the PPARgamma inhibition and Wnt/LRP5/ beta-catenin signaling activation in the effects of Huogu I formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The main TCM function of HGF is to help invigorate the spleen (Pi) to clear dampness, resolve phlegm and activate blood circulation. Previous animal testing had found an allopathic effect of HGF on preventing steroid-treated animals from developing steroid-associated ONFH [17,18]. Interestingly, we found that HGF also helps improve lipoprotein metabolism [17,18].…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…The main TCM function of HGF is to help invigorate the spleen (Pi) to clear dampness, resolve phlegm and activate blood circulation. Previous animal testing had found an allopathic effect of HGF on preventing steroid-treated animals from developing steroid-associated ONFH [17,18]. Interestingly, we found that HGF also helps improve lipoprotein metabolism [17,18].…”
Section: Introductionsupporting
confidence: 51%
“…Previous animal testing had found an allopathic effect of HGF on preventing steroid-treated animals from developing steroid-associated ONFH [17,18]. Interestingly, we found that HGF also helps improve lipoprotein metabolism [17,18]. Further experiments found that the ethyl acetate fraction of HGF helps inhibit the adipogenic differentiation of the bone marrow stromal cells [19] whereas the aqueous fraction of HGF promotes the osteogenic differentiation [20].…”
Section: Introductionmentioning
confidence: 51%
“…PPARγ is an adipogenic transcription factor that is expressed in the very early stage of adipogenesis35. This factor strongly promotes adipogenic differentiation and inhibits osteogenic differentiation36. Research has shown that steroids significantly up-regulate PPARγ expression in rodent and human BMSCs, leading to the time- and dose-dependent induction of adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐specific finite element models (FEM) of these participants were generated based on these CT images. All patients received non‐surgical management, including traditional Chinese medicine (TCM) herbal medication (Jianpihuogu Formula) for 180 days and restricted weight bearing with two crutches for 1 year. Table shows baseline data for the 40 participants.…”
Section: Methodsmentioning
confidence: 99%